The city Achir capital of the Zirid state in the Central Maghreb 324AH / 935 AD - mouchmouche, Mohamed (The Algerian Historical Journal, 2026)
Founded in the central Maghreb at the beginning of the century of 4AH/10AD several cities, played a major role in the urban and intellectual movement of the central Maghreb. The Sanhaja tribe also established the first Berber city in the central Maghreb (Asheer) in the shadow of Islamic civilization. She greatly contributed to the extension of Fatimid and Sanhaji influence in the Islamic Maghreb. She also played a major role in the urban development and architectural development of the cities of central Morocco, and inherited many cities that were founded after her, in particular the city of Qal'at Bani Hammad, and the archaeological evidence preserved in the national museums are the best witness to this. This research aims to introduce the political history and urban development of the city of Asher, and to highlight its urban expansion from the era of Ziri bin Manad until its destruction under the era of the Almohad state.